Nonlinear oscillations in disconjugate forced functional equations with deviating arguments - Bhagat Singh (International Journal of Mathematics and Mathematical Sciences)
For the equation Lnv(t)+a(t)h(y(g(t)))=f(t) where Lny(t)=pn(t)(pn−1(t)(…(p1(t)(po(t)y(t))′)′…)′)′ sufficient conditions have been found for all of its solutions to be oscillatory. The conditions found also lead to growth estimates for tle nonoscillatory solutions.